Freeletics As Sports Activities Community Recreation (Phenomenological study of community groups that carry out recreational sports in the city of Yogyakarta) - Ahmad Nizamuddin Shiddiq; Agus Kristiyanto; Muchsin Doewes (Kazimierz Wielki University, 2019)
This study aims to describe the phenomenon, the motives of the people, the enthusiasm of the people, the benefits of freeletics sports activities in the city of Yogyakarta. This type of research is qualitative research with a phenomenological approach. The informant retrieval technique uses the Snowball Sampling technique. The technique of collecting data uses observation, interviews, and document analysis. The data validity technique uses two triangulation techniques, namely data triangulation and method triangulation. Data analysis was carried out in four stages, namely: the stage of data collection, the data reduction stage, the data presentation stage, the stage of drawing conclusions. The results showed that Freeletics is a sport that focuses on body weight or body weight. For basic freeletics movements namely jumping jacks, squats, burpees, leg raises, push-ups, sit-ups and runs. The motive of the community is to participate in freeletics sports in the city of Yogyakarta, namely: want to maintain a healthy body, want to get an ideal body, want to tighten the muscles of the body, want to get happiness and recreation. Enthusiastic of the people of Yogyakarta City are quite high towards freeletics activities even though this sport is a new sport in the city of Yogyakarta. The benefits of freeletics are as a sports medium for maintaining health, recreation, adding friends, in addition to saving money can also get the ideal body.